2011
DOI: 10.5402/2011/486512
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Demographics of Slipped Capital Femoral Epiphysis

Abstract: The etiology of slipped capital femoral epiphysis (SCFE) is unknown with many insights coming from epidemiologic/demographic information. A systematic medical literature review regarding SCFE was performed. The incidence is 0.33/100,000 to 24.58/100,000 children 8 to 15 years of age. The relative racial frequency, relative to Caucasians at 1.0, is 5.6 for Polynesians, 3.9 for Blacks, and 2.5 for Hispanics. The average age is 12.0 years for boys and 11.2 years for girls. The physiologic age when SCFE occurs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 131 publications
7
138
2
4
Order By: Relevance
“…However there are several reports of asymptomatic cases, as it was demonstrated in a study in 2072 healthy Norwegian young people (18-20 years old) that found 6.6% cases of silent radiological SCFE (6). The reported incidence is variable depending on the countries, oscillating between 0.2 and 24.5:100,000 children 8 to 15 years old (1, 3,5), but this number may underestimate the real incidence due to silent forms (7). SCFE is more frequent during the adolescent growth spur that happens to an average age of 13.5 years in boys and 12 years in girls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However there are several reports of asymptomatic cases, as it was demonstrated in a study in 2072 healthy Norwegian young people (18-20 years old) that found 6.6% cases of silent radiological SCFE (6). The reported incidence is variable depending on the countries, oscillating between 0.2 and 24.5:100,000 children 8 to 15 years old (1, 3,5), but this number may underestimate the real incidence due to silent forms (7). SCFE is more frequent during the adolescent growth spur that happens to an average age of 13.5 years in boys and 12 years in girls.…”
mentioning
confidence: 99%
“…SCFE is frequently bilateral, reaching 50% of cases in some series. In unilateral cases, the age of presentation is usually younger, left hip is affected twice as often than the right, and an increased risk of contralateral damage appears in the next 18 months (3,8). It is important to always check the contralateral hip as some series describe 40% prevalence of asymptomatic slips in this Reumatismo 1/2016 Reumatismo, 2016;68 (1): [40][41][42][43][44][45][46][47] case report N o n -c o m m e r c i a l u s e o n l y Slipped capital femoral epiphysis in adults: case report and review of literature CASE REPORT location (6).…”
mentioning
confidence: 99%
“…7 Recent studies of the biomechanics of femoroacetabular impingement indicate that small anatomical deformities of the hip arising from SCFE can potentially cause permanent acetabular chondral damage. 4 Ganz et al 8 described the use of surgical dislocation of the hip when performing modified Dunn's osteotomy (subcapital realignment) in the treatment of unstable 9 and/or high-grade 3 SCFE.…”
Section: Discussionmentioning
confidence: 99%
“…Slipped capital femoral epiphysis (SCFE) is traditionally defined as the displacement of the femoral head in respect to the femoral diaphysis [1][2][3]. However, the real displacement is carried out by the femoral neck and the shaft as the head remains in the acetabulum because of the ligamentum teres [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of SCFE is unknown in most of the patients [1][2][3]7]. However, various risk factors have been reported to play a major role in abnormal increases in physeal solicitations or weakening of the growth plate in the presence of normal loading [1][2][3]8], resulting in the mechanical failure of the physis and the subsequent displacement of the femoral neck and shaft.…”
Section: Introductionmentioning
confidence: 99%